Morphological characterization and effect of meteorological factors on development of cucumber powdery mildew - K.R. SHYAM and RAMESH BHARDWAJ, S.K. GUPTA, AMITA GUPTA, (Indian Phytopathology, 2002)
Samples of powdery mildew of cucumber collected from different areas of Himachal Pradesh revealed the presence of anamorphs but for cool and dry temperate areas of Kinnaur, which contained teliomorphs besides anamorphs. On the basis of anamorphic characters like ellipsoidal conidia, presence of fibrosin bodies, germinating conidia produced both simple and forked germtubes and absence of appressorial formation and teliomorphic characters like cleistothecia with myceloid appendages, single ascus with eight ascospores, the fungus inciting the disease was identified as Sphaerotheca fuliginea (Schlecht.) Pollaci. The conidial germination was maximum at 25Â°C temperature and 100 per cent relative humidity. Moderate temperature of 25Â°C coupled with high relative humidity (> 95%) and reduced sunshine hours helped significantly in disease development.